Improved CsPbBr3 Light-Emitting Diodes with Sodium Trifluoroacetate Additive. (1st March 2023) - Hao, Xiaoming; Si, Junjie; Zhao, Hong; Liu, Zugang
Abstract: The perovskite light emitting diodes (PeLED / PeLEDs) possess the high efficiency and the wonderful color purity properties. However, the poor operational stability has hindered its broader development and commercial application. Utilizing the all-inorganic perovskites to fabricate PeLEDs is considered useful for enhancing device stability. In contrast, the resultant perovskite crystals in the emissive film show large grain sizes and low photoluminance efficiency. In this work, the sodium trifluoroacetate additive is introduced into all inorganic perovskite films to passivate surface defects and control the growth of the CsPbBr3 crystal. This approach results in inorganic perovskites with smaller grains and uniform surface morphology, which enables improved device performance.